Maximizing the Use of Google Sites in Delivering Instruction in Physical Education Classes - Culajara, Carla Jobelle (Physical Education and Sports: Studies and Research, 2022)
Background: Being inventive and creative in offering effective and efficient teaching and learning processes is one of the priorities of any teacher, especially Physical Education teachers, as the delivery of instruction to students evolves. With these, this study proves and illuminates the usefulness of Google sites in delivering physical education teaching. Objectives: This research aims to determine the effects of Google sites as a medium for delivering Physical Education on the learning outcomes of Grade 10 students in one of the secondary schools in the Philippines. Its specific aims were to: (1) determine the impact of Google sites on availability, functionality, and goals, and (2) establish an enhancement program based on the study's findings. Methods: The study utilized a quantitative research design with descriptive approach accompany with survey questionnaire. The purposive sampling was utilized to 106 students from secondary schools in the Philippines.  Results: As the findings of the study geared toward its effectiveness in terms of functionality, availability and learning experience, it shows that most of the lessons delivered and maximizing Google sites as a tool in delivering instruction were appreciated by the students where students were mostly “Strongly Agree” with the responses. With this tool in delivering instruction, it shows light that students can easily understand the lesson in learning and doing tasks using Google sites. Conclusion: This study sheds light on the effective and efficient use of Google sites in delivering instruction in PE classes particularly offers a safe learning virtual environment, accessibility to the learning materials and learned using their own time and autonomy in learning. Using Google Sites to the fullest extent possible in Physical Education classes.